On the characteristics of various Quranic recitation for lossless audio coding application - Gunawan, Teddy Surya; Kartiwi, Mira (IEEE, 2016)
Nowadays, there are more than 500 Quranic recitations available freely on the Internet. Most of the audio files were recorded in MP3 format due to its popularity, but lossless audio coding has gained much interest due to its high quality. The drawback of the lossless audio coding is the higher bitrate requirement. In this paper, the characteristics of the Quranic recitation of all surahs from various Reciters were evaluated. Results show that on average the voiced to unvoiced speech ratio is 21.39 for Quranic recitation, while the English audiobook on average has ratio of 7.49. It means that the voiced speech is more dominant compared to unvoiced speech in Quranic recitation. It is expected that the linear predictor component in a typical lossless audio compression could be optimized further so that efficient representation of Quranic audio signal could be achieved.